Modernity, the principles of public welfare (mas̨las̨a) and the end goals of shari'a (maqas̨id) in Muslim legal thought - Abderkader, Deina (Islam and Christian-Muslim relations, 2003)
Modernity is often assumed to be a unilateral schema that everybody could follow. This essay examines the adaptability of certain notions embedded in the literature about development in the Muslim world. The discourse on modernity in Muslim societies has taken shape mostly post World War II after the Muslim nations asserted their independence, and it has continued till contemporary times. How did this discourse change over the years? How did the exchange of ideas also affect the Muslim 'other'? Are there common grounds between 'modernity' and Islamic legal percepts (which are central to Muslim political thought)? This essay will examine these queries and discuss the importance of the principle of 'Public Welfare' in our contemporary discourse on modernity in Muslim societies.